Timing Is Everything: Acoustic Niche Partitioning in Two Tropical Wet Forest Bird Communities - Hart, Patrick J.; Ibanez, Thomas; Paxton, Kristina; Tredinnick, Grace; Sebastián-González, Esther; Tanimoto-Johnson, Ann (Frontiers in Ecology and Evolution, 2021)
When acoustic signals sent from individuals overlap in frequency and time, acoustic interference and signal masking may occur. Under the acoustic niche hypothesis (ANH), signaling behavior has evolved to partition acoustic space and minimize overlap with other calling individuals through selection on signal structure and/or the sender’s ability to adjust the timing of signals. Alternately, under the acoustic clustering hypothesis, there is potential benefit to convergence and synchronization of the structural or temporal characteristics of signals in the avian community and organisms produce signals that overlap more than would be expected by chance. Interactive communication networks may also occur, where species living together are more likely to have songs with convergent spectral and or temporal characteristics. In this study, we examine the fine-scale use of acoustic space in montane tropical wet forest bird communities in Costa Rica and Hawai‘i. At multiple recording stations in each community, we identified the species associated with each recorded signal, measured observed signal overlap, and used null models to generate random distributions of expected signal overlap. We then compared observed vs. expected signal overlap to test predictions of the acoustic niche and acoustic clustering hypotheses. We found a high degree of overlap in the signal characteristics (frequency range) of species in both Costa Rica and Hawai‘i, however, as predicted under ANH, species significantly reduced observed overlap relative to the random distribution through temporal partitioning. There was little support for acoustic clustering or the prediction of the network hypothesis that species segregate across the landscape based on the frequency range of their vocalizations. These findings constitute strong support that there is competition for acoustic space in these signaling communities, and this has resulted primarily in temporal partitioning of the soundscape.